Islamic Religious Education Teacher of Learning Strategy in Implementing Religious Values Through Whatsapp - Ashif Az Zafi; Maulida Tsalis Maroh; Siswanto Siswanto; Irwan Fathurrochman (Nazhruna: Jurnal Pendidikan Islam, 2021)
This article aims to describe the strategies used by Islamic Religious Education teachers in instilling religious values ​​when teaching students in the midst of a pandemic that is currently sweeping the world. This causes the learning system that is usually done directly or face-to-face to become online. This study uses a qualitative method, which describes the facts and phenomena that occur in the field. The Covid-19 virus, which originated in Wuhan, China, has a very rapid spread and has an impact on the whole world, one of which is Indonesia. The State Civil Apparatus (ASN) as well as strata of society feel the consequences themselves, especially in the field of education, which causes schools to carry out the learning process at home or online. PAI teachers as educators must rack their brains about strategies in teaching students which are usually carried out face-to-face to online or online. In order to respond to this, there is a solution to what teachers can do, namely by using the WhatsApp media. With WhatsApp that is easy to access, it is hoped that teachers in delivering learning can be accepted and understood and do not reduce in terms of instilling religious values ​​of students.